Estimativa de parâmetros genéticos de caracteres de produção e de aparência de tubérculo de batata (Solanum tuberosum L.) - Ney, Vicenti Gonçalves (2012)
Yield components and tuber appearance components constitute the two trait groups primarily considered in potato selection. Therefore, the establishment of selection criteria for these characters is essential for defining the strategies for breeding. The choice of parents and trait selection in early generations, when carefully defined and incorporated as a practice in breeding programs, increase efficiency and reduces the cost of developing new cultivars. The objectives of this research were (i) to estimate genetic variability, heritability and expected selection gain for yield components and tuber appearance in early generations, and (ii) to investigate the relationship between phenotypic traits assessed in tubers of potato families in the seedling and the first clonal generation. Twelve potato families were obtained from artificial crosses between two genotype groups: Eliza, C1730-7-94 and C1742-8-95; and Shepody, Asterix, White Lady and Caesar. Crosses were made in factorial mating design (3x4). Each family was constituted of 75 genotypes, distributed a randomly block design with three replications of 25 genotypes per plot. The 12 families were evaluated in the seedling generation, grown in greenhouse, and in the first clonal generation, grown in the field, in autumn season of 2010 and 2011, respectively. The families were evaluated for the following traits: skin roughness (ASP), eye depth (OLH), eyebrow prominence (SOB), tuber shape (FOR), uniformity of tuber shape (UFO), tuber pointing (APO), tuber curvature (CUR), tuber flatness (ACH), uniformity of tuber size (UTA), and tuber appearance (APA), components of overall tuber appearance; tuber number (NTU), total tuber mass (MAS), and average tuber mass (MAM), components of tuber yield. The analysis of variance detected no significant family X generation interaction for the following tuber trait components: OLH, SOB, UFO, CUR, ACH, APA, and TAM. The interaction was significant for FOR, APO, UTA, NTU, MAS, and MAM. Heritability estimates ranged from moderate to high in the joint analysis of the seedling generation and first clonal generation, for traits that showed no interaction between generations. The estimates were high for OLH, SOB, CUR, and ACH; moderately high for APA and UFO; and low for TAM. These results indicate the possibility of moderate to strong intensity selection at the seedling generation for these traits, except for TAM. Significant correlations between tuber general appearance traits (in both generations) were moderate for OLH x ASP, CUR x ACH e CUR x UFO; moderate to strong for ASP x APA and CUR x FOR; and strong to very strong for CUR x APO and SOB x OLH. Correlations between yield traits was strong for MAS x NTU; moderate for MAM x NTU and MAM x MAS. The correlations between the seedling generation and the first clonal generation was high for OLH, and moderate for SOB, CUR, ACH, NTU, and MAS, suggesting that selection for these traits could be made in the seedling generation.